2021
DOI: 10.3390/pharmaceutics13122074
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Concentrations in Mothers, Colostrum and Breastfed Infants during the Early Postpartum Period: Comparison with Concentrations Determined during Delivery and in the Mature Milk Period

Abstract: To obtain information on the transport of valproic acid from mothers to colostrum and breastfed infants, in this cohort study, valproic acid concentrations in maternal serum (90 subjects), colostrum and the serum of breastfed infants were analyzed in years 1993–2018, between the 2nd and 5th postnatal days. Valproic acid concentrations ranged from 4.3 to 66.5 mg/L (mean 31.2 ± 13.6 mg/L) in maternal serum, from 0.5 to 5.9 mg/L (mean 1.1 ± 1.2 mg/L) in milk, and from 0.5 to 42.9 mg/L (mean 15.4 ± 9.4 mg/L) in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…VPA is excreted into human milk in relatively low concentrations [ 95 , 96 , 97 ]. Available reports suggest that a suckling infant may ingest less than 5% of the weight-adjusted maternal daily dose [ 93 ].…”
Section: Vpa Transplacental Passage and Secretion Into Milk And Semenmentioning
confidence: 99%
See 1 more Smart Citation
“…VPA is excreted into human milk in relatively low concentrations [ 95 , 96 , 97 ]. Available reports suggest that a suckling infant may ingest less than 5% of the weight-adjusted maternal daily dose [ 93 ].…”
Section: Vpa Transplacental Passage and Secretion Into Milk And Semenmentioning
confidence: 99%
“…Available reports suggest that a suckling infant may ingest less than 5% of the weight-adjusted maternal daily dose [ 93 ]. Kacirova et al [ 95 ], in a study carried out in 2021 women, examined the VPA concentrations in breast milk and newborn serum and found that the infant serum concentrations and maternal concentrations in milk are low, ranging from 0.01 to 1.61, with an average of 0.51. Hence, lactation by VPA-treated mothers is permissible.…”
Section: Vpa Transplacental Passage and Secretion Into Milk And Semenmentioning
confidence: 99%